Frequency offset estimator for OFDM with time-frequency training sequence - JIANG Yan-xiang; WANG Dong-ming; GAO Xi-qi; YOU Xiao-hu (Tongxin xuebao)
A ratio-adjustable time-frequency training sequence was proposed.The coarse carrier frequency offset（CFO） estimation was accomplished with the aid of the training sequence in frequency domain and a predefined lookup table,while the fine one was obtained by the aid of the training sequence in time domain.Simulation results show that the per-formance of the proposed method is better than Lei’s method with almost the same overhead.However,its computational complexity is much lower than Lei’s.